CLINICAL EVIDENCE IN MEDICAL DEVICE PERFORMANCE: MAIN CHALLENGES - Miguel Antunes; Mariana Pereira; Pedro Durão (Formifarma, LDA., 2012)
Problems underlying the question of clinical evidence in medical device performance have been the subject of critical review in several reference journals of the medical field. And yet, the demand for higher methodological studies is increasing, considering that they will determine, on a first phase, the market authorization of the device and, on a second phase, its adoption within a health system scheme based on its added therapeutic value in comparison with alternative therapeutic methods, a core component of the Health Technology Assessment process. This paper tries to identify some of the most frequently mentioned shortcomings in the scientific literature regarding the production of clinical evidence regarding the benefits of using a certain medical device, and some of the new strategies that are being considered as possible solutions for such constraints.